Ecological assessment of lake Akbas by hydrophysical, hydrochemical and algological indicators (ҚазҰУ хабаршысы. Экология сериясы, 2021)
This paper evaluates the results of hydrophysical and hydrochemical indicators of Lake Akbas ofthe Kokshetau State National Natural Park, which belongs to the category of specially protected naturalareas. Changes in the lake area over a period of about 50 years are shown. In terms of water color andturbidity, there has been a decrease over the past 3 years. The area of the Akbas lake basin has decreasedby 15.3% over the past 50 years. During the study period, the content of dry waste in the lake waterexceeded the MAC by 1.1–1.5 times annually. Lake Akbas is moderately polluted in 2018-2019 in termsof the level and quality of class III pollution. However, it was found that some hydrochemical parametersexceed the MAC. Along with the hydrophysical and hydrochemical indicators of Lake Akbas, we identified the species composition of microalgae in the lake, seasonal changes and conducted a systematicanalysis. As a result of the study, the algae flora of Lake Akbas consisted of 61 species, 20 of which areindicator-saprobic microalgae. To study the sensitivity of algae to environmental factors and variouschemical reactions, we carried out biotesting of water samples from Lake Akbas. Biotesting showedthat the Chlorella sp-3K strain is moderately sensitive to toxic concentrations in Lake Akbas. Researcheshave shown that bioassays for microalgae in lake water are quick and easy and complement the resultsof chemical studies. According to the results of hydrophysical, hydrochemical studies and biotesting ofalgocenoses, it was determined that the water of Lake Akbas belongs to 3 classes of pollution.Key words: Нydrophysical and hydrochemical indicators, algoflora, biotesting.